Diagnostic Accuracy of Clinical Tests and Imaging Exams for Femoroacetabular Impingement: An Umbrella Review of Systematic Reviews. Issue 6 (17th November 2022) - Fernandes, Daniel A.; Melo, Gilberto; Contreras, Marcos E. K.; Locks, Renato; Chahla, Jorge; Neves, Fabricio S.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To synthesize available evidence about diagnostic accuracy of clinical tests and imaging examinations for femoroacetabular impingement (FAI) syndrome. Design: Umbrella review. Setting: N/A. Participants: N/A. Interventions: N/A. Main Outcome Measures: Systematic reviews (SR) indexed in Embase, LIVIVO, PubMed, SCOPUS, the Cochrane Library, and Web of Science were searched in a 2-phase process. SR assessing diagnostic accuracy were considered eligible. Results: From 1520 studies, 6 SR were included, which evaluated 24 primary studies related to FAI syndrome. Of these, 5 SR assessed clinical tests, and a substantial heterogeneity was found concerning reference standards adopted across primary studies, which included arthroscopy, clinical examination (associated or not with imaging exams), intra-articular injections, and open surgery. Most clinical tests presented higher values of sensitivity compared with specificity, although evidence was considered limited because the same primary studies were often included across SR. Nonetheless, evidence around the flexion adduction internal rotation (FADIR) test was considered stronger and its use as a screening tool was consistently supported. Only one SR assessed the accuracy of imaging examinations, which adopted open surgery as the sole reference standard. Most imaging exams presented considerably high values of sensitivity, although specificity values were notably lower. Conclusions: No robust recommendations can be provided for most clinical tests, although the FADIR test, in particular, was consistently supported as a screening tool. Moreover, although imaging examinations showed considerably high sensitivity values, evidence was considered sparse and further research is strongly recommended to validate its use as reference standards for diagnostic accuracy data.